2014
DOI: 10.1111/ecc.12247
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patient experience with navigation service in an urban hospital setting: a qualitative study

Abstract: Cancer patient navigators are increasingly present on the oncology health care team. The positive impact of navigation on cancer care is recognised, yet a clear understanding of what the patient navigator does and how he/she executes the role continues to emerge. This study aimed to understand cancer patients' perceptions of, and experiences with patient navigation, exploring how navigation may enhance the patient experience in an urban hospital setting where patients with varying needs are treated. A qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The issue of trust is a vital component to building a therapeutic relationship (Arnold & Underman Boggs, ). The importance of establishing a trusting relationship with the navigator coincides with other literature on patients’ experience of navigation (Carroll, Humiston, Meldrum, Salamone, & Jean‐Pierre, ; Fischer, Sauaia, & Kutner, ; Gotlib Conn, Hammond Mobillio, Rotstein, & Blacker, ). Carroll et al.…”
Section: Discussionsupporting
confidence: 80%
“…The issue of trust is a vital component to building a therapeutic relationship (Arnold & Underman Boggs, ). The importance of establishing a trusting relationship with the navigator coincides with other literature on patients’ experience of navigation (Carroll, Humiston, Meldrum, Salamone, & Jean‐Pierre, ; Fischer, Sauaia, & Kutner, ; Gotlib Conn, Hammond Mobillio, Rotstein, & Blacker, ). Carroll et al.…”
Section: Discussionsupporting
confidence: 80%
“…Another key finding that emerged from the data was system-level challenges to offering support stemming from a lack of housing resources. Although housing navigation may not overcome challenges to waitlists, individuals experience navigation as a means of demystifying complex systems 28 to make the existing services easier to access and advocate for public policy that reflects housing as health. With this said, it is important to recognize that housing patient navigators will need to acquire experience and service knowledge over time that allows them to recommend appropriate services.…”
Section: Discussionmentioning
confidence: 99%
“…The navigation role provides a measure of security and familiarity through continuity of care and integrates multiple areas of care coordination, including streamlining medical appointments, providing education and assisting with access to financial services and psychological support throughout and following treatment [44,45]. In cancer care, research shows that patients who had access to PNs reported fewer problems with care and improved delivery of PCC [46,47]. There are several barriers to implementation of PNs, including availability of trained PNs, distribution of PNs across rural or remote regions, and health care costs associated with use of PNs.…”
Section: Discussionmentioning
confidence: 99%